VARIASI KELUASAN MAKNA PENGALAMAN DALAM PENERJEMAHAN NOVEL RONGGENG DUKUH PARUK KE DALAM BAHASA INGGRIS - Khristianto, Khristianto (Sunan Kalijaga State Islamic University Yogyakarta, 2018)
There is no “real equivalence” in translation; it is always relative, finding the best among the defect possibilities. This study was aimed to discover the the types of variations of the experiential meaning breadth (EMB) in a novel, 'Ronggeng Dukuh Paruk' in Indonesian and English, to find out the EMB variation level.This is a descriptive qualitative endevour, applying a content analysis method, focusing on the experiential meaning, particularly on its breadth dimension. The data sources are two language versions of the novel, Indonesian (Ind) and English (En). The data are clause units of transitivity. The results of this study indicate that the most dominant EMB variation is 0 variation. The intertextual bond is proved to be strong in leading the translators to create the meaning of the clauses. In general the variation level of EMB is very low, 9.16. This indicates that the intertextual context plays a very dominant role to lead the decision of the translator in realizing the meaning. The variations in the EMB in general do not affect the completeness of the meaning.